Critical development studies handbook - "Meyer, Henryvelt.(ed.)" (London, 2011)
This handbook provides a clear and accessible introduction to the groundbreaking and interdisciplinary new field of critical development studies. Each short chapter is written by a well-known specialist and provides a succinct discussion of central issues in the field. It provides a critical perspective informed by a belief in the need for substantive change and for genuine, lasting progress in international development. This will be an important resource for all development scholars, teachers, students, researchers and activists who want to practice Development Studies with a critical edge.
Keywords: Economic development